30 years on: A brave new world or an unfolding disaster? - Turner, Stuart (Torture Journal, 2022)
In this short essay, the focus is on social and political aspects of forced migration. It is argued that policies designed to restrict access to developed countries have, rather like the American “prohibition”, produced a thriving criminal market for smugglers, in this case of people. Making travel more difficult increases both their profits and the sophistication of their methods. Provision of targeted, properly controlled, support for refugees in countries neighbouring conflict zones might help to reduce the pressure on travel to Europe and could be both more successful and more humanitarian. For those who do reach developed countries, there is scope to improve the legal decision-making process. Psychological input should include scientific investigation of legal assumptions, and the provision of relevant expert literature reviews, for example concerning modern knowledge of memory. Trust is the first casualty of repressive violence, and mistrust among opposition groups is probably one of the key mechanisms of its success. We need to make sure that we do not provide further grounds for this sort of reaction. Although there is no brave or new world ahead, we must continue to confront ignorance and prejudice, as we seek to avoid more humanitarian disasters. It is now just over thirty years since we published a potential framework for understanding how survivors of organised state violence react to complex and severe trauma (Turner & Gorst-Unsworth, 1990). We argued that no single psychological process underpins the reactions to this experience, and therefore, there can be no unitary torture syndrome, but rather a series of understandable psychological pathways activated to varying degrees by different experiences, leading to diversity of emotional response, with implications for recovery and treatment. We also asked family doctors about health needs of refugees (Ramsay & Turner, 1993), and it is wonderful to see how the evidence on treatment options has developed since then, especially in recent years. In this paper, looking back over the last thirty years, in celebration of the anniversary of Torture journal, I will focus on political, legal and forensic aspects of forced migration.